Social Media’s Role in the Changing Religious Landscape of Contemporary Bangkok - Ruchi Agarwal (2022)
In this article, the authors argue that social media is becoming a more influential medium for religious services in Bangkok, Thailand. Buddhism, with an attendant mixing of Thai animistic beliefs in spirits, inanimate objects, and talismans, along with other expressive forms of religious enterprise, is adapting to a changing personalized media landscape to reach ever more diverse audiences. Social media in particular is allowing for social and personal entrepreneurship of religious expressions that formerly were largely limited by physical space and its attendant costs. The authors argue that utilizing the Uses and Gratification approach will provide a powerful method for understanding and evaluating how and why religious entrepreneurship is shifting in contemporary Thailand.